Complement and Lysozyme Requirements for Spirochetolysis in Guinea Pig Serum - Nevin, T. A. (1967)
During experiments on the immunological immobilization of treponemes, several cultured strains were lysed in the guinea pig serum used as a source of complement. In further studies employing Borrelia vincentii, lysis, observed by darkfield, appeared as swelling and some beading of the cells. Complete disruption eventuated. Untreated guinea pig serum was strongly lytic, whereas little or no lysis occurred in bentonite-adsorbed samples. Activity was restored to these samples by adding commercially obtained crystalline egg-white lysozyme. Serum samples which had been heated, absorbed with aggregates of human γ-globulin, or treated with ethylenediaminetetraacetate to remove, or inactivate, complement also lost spirochetolytic activity.